HISTORICAL INTERPRETATION OF SOCIETAL COHESION IN TAMIL TEMPLES: - V. Biresan; V. Thirumurugan (RADJA PUBLIKA, 2024)
This study delves into the historical significance of Tamil temples as crucial loci of societal cohesion, transcending their primary role as places of worship. Functioning as multifaceted institutions, Tamil temples have historically unified communities through their contributions to education, the arts, economic activities, and cultural preservation. This research critically examines their capacity to foster harmony among diverse social strata while simultaneously embodying and influencing the hierarchical framework of Tamil society. Through an interdisciplinary scrutiny of architectural features, epigraphic records, and ritual practices, the study unveils the complex interplay between tradition and societal structure within these sacred spaces. By situating Tamil temples at the nexus of cultural identity and social integration, this work offers a nuanced understanding of their enduring legacy in navigating the intricate dynamics of caste, tradition, and cultural transformation.